Multivalent MVA-vectored vaccine elicits EBV neutralizing antibodies in rhesus macaques that reduce EBV infection in humanized mice - Escalante, Gabriela M.; Reidel, Ivana G.; Mutsvunguma, Lorraine Z.; Cua, Simeon; Tello, Brenda A.; Rodriguez, Esther; Farelo, Mafalda A.; Zimmerman, Cloe; Muniraju, Murali; Li, He; Govindan, Aparna N.; Axthelm, Michael K.; et al. (Frontiers in Immunology, 2024)
Epstein-Barr virus (EBV) is an oncogenic human herpesvirus associated with ~350,000 cases of lymphoid and epithelial malignancies every year, and is etiologically linked to infectious mononucleosis and multiple sclerosis. Despite four decades of research, no EBV vaccine candidate has yet reached licensure. Most previous vaccine attempts focused on a single viral entry glycoprotein, gp350, but recent data from clinical and pre-clinical studies, and the elucidation of viral entry mechanisms, support the inclusion of multiple entry glycoproteins in EBV vaccine design. Here we describe the generation and characterization of a modified vaccinia Ankara-vectored EBV vaccine, MVA-EBV5-2, that targets five EBV entry glycoproteins, gp350, gB, and the gp42gHgL complex. The vaccine was genetically and translationally stable over 10 viral passages as shown by genetic and protein expression analysis, and when administered to female and male BALB/c mice, elicited serum EBV-specific IgG of both IgG1 and IgG2a subtypes with neutralizing activity in vitro. In Raji B cells, this neutralizing activity outperformed that of serum from mice immunized with a monovalent MVAvectored gp350 vaccine. Similarly, MVA-EBV5-2 elicited EBV-specific IgG in lymphocryptovirus- negative rhesus macaques that were detected in both serum and saliva of immunized animals, with serum antibodies demonstrating neutralizing activity in vitro that outperformed serum from MVA-gp350-immunized macaques. To test whether MVA-EBV5-2-elicited serum antibodies had neutralizing potential in vivo, serum from immunized macaques was passively transferred to human CD34+ hematopoietic stem cell-reconstituted NSG mice, followed by EBV challenge. In two independent experiments using a low and a high EBV challenge dose, pre-treatment with serum from MVA-EBV5-2-immunized macaques resulted in fewer EBV-infected mice than pre-treatment with serum from pre-immune macaques or macaques immunized with the monovalent gp350-based vaccine. These results support the inclusion of multiple entry glycoproteins in EBV vaccine design and position our vaccine as a strong candidate for clinical translation.